The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.3390/ani13132124
|View full text |Cite
|
Sign up to set email alerts
|

Acoustic Monitoring of Professionally Managed Marine Mammals for Health and Welfare Insights

Abstract: Research evaluating marine mammal welfare and opportunities for advancements in the care of species housed in a professional facility have rapidly increased in the past decade. While topics, such as comfortable housing, adequate social opportunities, stimulating enrichment, and a high standard of medical care, have continued to receive attention from managers and scientists, there is a lack of established acoustic consideration for monitoring the welfare of these animals. Marine mammals rely on sound productio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 122 publications
0
5
0
Order By: Relevance
“…Fortunately, researchers and animal management staff who have the means to purchase recording equipment and software are able to take advantage of recent technological advances in the field of bioacoustics. Modern acoustic monitoring systems make it possible for researchers to continuously track individuals under a variety of circumstances (e.g., in the dark, underwater, after-hours), even for group-housed or nocturnal animals (126,127). Before initiating a study, a considerable amount of effort must be invested in weighing options for recording and analyzing calls.…”
Section: Methodological Considerations and Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fortunately, researchers and animal management staff who have the means to purchase recording equipment and software are able to take advantage of recent technological advances in the field of bioacoustics. Modern acoustic monitoring systems make it possible for researchers to continuously track individuals under a variety of circumstances (e.g., in the dark, underwater, after-hours), even for group-housed or nocturnal animals (126,127). Before initiating a study, a considerable amount of effort must be invested in weighing options for recording and analyzing calls.…”
Section: Methodological Considerations and Limitationsmentioning
confidence: 99%
“…Similarly, the National Marine Mammal Foundation's Welfare Acoustic Monitoring System (WAMS) employs hydrophones to continuously capture, count, and localize vocalizations, as well as specialized software that automatically compares the current data to historical output/baseline data. In fact, this real-time alert system includes an alarm module that triggers an email alert (complete with a call count, screenshot of the spectrogram, and localization information) if the call rate surpasses the user-defined threshold (127,131). For farm animals, Briefer et al (29) demonstrated that an automated recognition system allowed for real-time discrimination of valence, as well as the context of call production.…”
Section: Methodological Considerations and Limitationsmentioning
confidence: 99%
“…Given the importance of sound production and processing to the behaviours of dolphins, it is important to create an appropriate acoustic environment when assessing dolphin welfare holistically [ 83 , 84 ]. Therefore, sound measurements play a crucial role in the care of dolphins to determine whether an appropriate acoustic environment is provided.…”
Section: Final Toolmentioning
confidence: 99%
“…The effects on hearing were only induced by repeated exposure to intense sonar pulses with total sound exposure levels of 214 dB re: 1 μPa2 s. The exposures also triggered slight behavioural changes. In general terms, it is advisable to measure all these factors by taking regular sound level measurements or implementing an acoustic monitoring system [ 84 , 87 ]. With this approach, changes in the soundscape of the animals that could affect welfare can be assessed more quickly.…”
Section: Final Toolmentioning
confidence: 99%
See 1 more Smart Citation